Evaluation 172 patients of submandibular gland swelling with a case of adenocarcinoma, not otherwise specified: a needle in a haystack - Agarwal, Navneet; Ahuja, Paridhi; Agarwal, Sukriti; Dhawal, Ayushi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Aim of the study was to assess the patients of submandibular gland pathology and to describe a case of adenocarcinoma, not otherwise specified (ANOS) of the submandibular gland in terms of clinical presentation, diagnosis, line of management and prognosis. Methods: The study was conducted as a retrospective review of all the patients who underwent submandibular gland excision in the last 6 years at the department of otorhinolaryngology, M.D.M. hospital, Dr. S.N. Medical college, Jodhpur. The records were assessed and statistically evaluated. Results: Out of 172 cases of submandibular gland excision, only 1 case of ANOS was seen. The rest included 134 cases were of chronic non-inflammatory process, 24 cases of sialolithiasis, 10 cases of metastasis from oral cavity cancer and 3 cases of primary squamous cell carcinoma. Fine needle aspiration cytology (FNAC) was not diagnostic in ANOS. Excision of the gland with primary closure was done. Adjuvant radiotherapy was given. Conclusions: ANOS has a rare occurrence in submandibular gland swelling and it is also very tricky to diagnose it. The nature of this malignancy is invasive and nodal metastasis is present. Surgical excision and post-op evaluation can be life-saving.